2006
DOI: 10.1348/147608305x52595
|View full text |Cite
|
Sign up to set email alerts
|

A naturalistic comparison of the effectiveness of trainee and qualified clinical psychologists

Abstract: A variety of factors (e.g. quantity of supervision) contributing to trainee effectiveness are identified and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…There are only a handful of studies focusing on psychotherapy education and the associated therapy clinics. However, there are some studies of the effects of CBT performed by therapist candidates with limited theoretical education, and the conclusions made in these studies seems to be that CBT performed by therapist candidates can be effective (Bados, Balaguer & Saldaña, ; Buckley, Newman, Kellett & Beail, ; Hiltunen, Kocys & Perrin‐Wallqvist, ; Lappalainen, Lehtonen, Skarp, Taubert, Ojanen & Hayes, ; Öst, Karlstedt & Widén, ).…”
Section: Introductionmentioning
confidence: 99%
“…There are only a handful of studies focusing on psychotherapy education and the associated therapy clinics. However, there are some studies of the effects of CBT performed by therapist candidates with limited theoretical education, and the conclusions made in these studies seems to be that CBT performed by therapist candidates can be effective (Bados, Balaguer & Saldaña, ; Buckley, Newman, Kellett & Beail, ; Hiltunen, Kocys & Perrin‐Wallqvist, ; Lappalainen, Lehtonen, Skarp, Taubert, Ojanen & Hayes, ; Öst, Karlstedt & Widén, ).…”
Section: Introductionmentioning
confidence: 99%
“…There is a gap in research because of a limited number of investigations of the effectiveness of training in terms of actual performance of psychology trainees in a university clinic setting. There is evidence to suggest that trainee psychologists in European training programmes produce similar (Buckley, Newman, Kellett, & Beail, ) or even superior clinical outcomes (Vollmer, Spada, Caspar, & Burri, ) to qualified psychologists. Similar findings were apparent in an American study that compared efficacy and efficiency of trainees to experienced therapists (Stein & Lambert, , ).…”
Section: Aimsmentioning
confidence: 99%
“…It was found that 90.7% of patients showed clinical improvement on a range of validated measures and that the treatment offered by trainees was on par with that of licenced psychotherapists (Öst et al., ). A naturalistic study from the UK found no significant difference between the effectiveness of treatment provided by psychology trainees ( n = 60) and qualified clinical psychologists ( n = 60) (Buckley, Newman, Kellet, & Beail, ). This attests to the effectiveness of this model in competency building.…”
Section: Psychology Training In Australiamentioning
confidence: 99%